Transformasi Ekonomi Lokal Era Society 5.0: Peluang dan Tantangan Program Desa Maju Inhil Jaya di Kabupaten Indragiri Hilir - Sultan Amra; Ghina Nabillah Effendi (Jurnal Ilmu Pemerintahan, 2024)
The transformation of local economies is crucial for achieving sustainable development, particularly in the era of Society 5.0, characterized by the integration of advanced technologies into various aspects of society. Indragiri Hilir Regency, through the Desa Maju Inhil Jaya (DMIJ) program, seeks to leverage the Society 5.0 concept to improve village welfare. However, the program faces significant challenges, including limited technological infrastructure and low digital skills among the rural population. Society 5.0, first introduced by the Japanese government in response to the Fourth Industrial Revolution, emphasizes the use of advanced technologies such as IoT, AI, big data, and robotics to create a more inclusive and sustainable society. This research aims to analyze the implementation of Society 5.0 within the DMIJ program and explore the opportunities and challenges encountered. The study employs a literature review method, synthesizing data from various secondary sources to provide comprehensive insights into the potential and obstacles of integrating advanced technology into local economic development initiatives. The findings suggest that digital technology can empower local communities by enhancing economic activities, participation, and human resource quality. Despite the challenges, the successful application of Society 5.0 principles in the DMIJ program can serve as a model for other regions, contributing to national development and improving the quality of life in rural areas.